Target Executive Equity-based Compensation and Shareholder's Wealth Effect in Leveraged Buy-outs - Bhatia, Rohit (2010)
I examine if providing more incentives in the form of Equity based compensation to top executives of target firm a right practice? Does EBC enhance shareholders wealth or give executives an opportunity to make personal gains. For this study, I collected 129 target companies acquisition from a sample of 217 deals taking place in the United States during period 1994-2008 . I investigate whether granting high Equity based compensation to target firm executives decreases shareholders wealth. This is due to acceleration of unvested option and removal of restriction in buyouts which may motivate the target firm executives to sell the firms for their own personal benefits. Using CAR, acquisition premium and termination fees as a substitute for shareholders wealth I found evidence of providing target executives equity based compensation has no impact on shareholders wealth